2020
DOI: 10.21203/rs.2.17433/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparative Efficacy of Neuraxial and General anesthesia for hip fracture surgery: A meta-analysis of randomized clinical trials

Abstract: Abstract Background: The choice of anesthesia technique remains debatable in patients undergoing surgical repair of hip fracture. This meta-analysis was performed to compare the effect of neuraxial (epidural/spinal) versus general anesthesia on perioperative outcomes in patients undergoing hip fracture surgery. Methods: Medline, Cochrane Library, Science-Direct, and EMBASE databases were searched to identify eligible studies focused on the comparison between neuraxial a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Questions could arise if this difference in the percentage of patients operated on with spinal anaesthesia could be of influence on the end result. However, until now the literature is not unambiguous about the advantages and disadvantages of spinal and general anaesthesia in hip fracture patients [46] .…”
Section: Article In Pressmentioning
confidence: 99%
“…Questions could arise if this difference in the percentage of patients operated on with spinal anaesthesia could be of influence on the end result. However, until now the literature is not unambiguous about the advantages and disadvantages of spinal and general anaesthesia in hip fracture patients [46] .…”
Section: Article In Pressmentioning
confidence: 99%
“…In addition, perioperative EA for major elective orthopaedic procedures may be associated with the reduction in odds of developing deep vein thrombosis, pulmonary embolism, transfusion requirements, pneumonia, respiratory depression, myocardial infarction and renal failure 13 . However, trials investigating patients with hip fracture have not found the same association 14‐16 …”
Section: Introductionmentioning
confidence: 99%